Implementasi MGMP sebagai Strategi Penguatan Kompetensi Guru di Community Learning Center (CLC) - Septiand, Wilddan Rezzy; Hariyati, Nunuk; Mustaji, Mustaji; Khamidi, Amrozi; Amalia, Kaniati; Nursalim, Mochamad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The Government of Indonesia, through the Sekolah Indonesia Kota Kinabalu (SIKK) and Community Learning Centers (CLCs), strives to fulfill the educational rights of children of Indonesian Migrant Workers (PMI) in Sabah, Malaysia. However, limitations in human resources, facilities, and geographical conditions pose significant challenges to the provision of education in the CLCs. One strategy to improve the quality of teaching and teacher competence is the implementation of Subject Teacher Working Group (MGMP) activities. This study aims to evaluate the effectiveness of implementation of MGMP and to identify its challenges and improvement strategies. The research employs a literature review method with a descriptive qualitative approach, analyzing twenty relevant publications published between 2020 and 2025. The analysis reveals that MGMP contributes positively to enhancing teachers' professional and pedagogical competencies, strengthening collaborative networks, and improving the quality of lesson planning and implementation. MGMP also reinforces teachers’ understanding of the curriculum and their ability to adapt instruction in multigrade classrooms. However, its effectiveness is still hindered by limited facilities, lack of structural support, low teacher participation, and weak program management. Therefore, strengthening MGMP institutions is necessary through facilitator training, integration with formal training programs, the development of supportive regulations, and the establishment of a data-driven evaluation system.